2000
DOI: 10.1126/science.287.5461.2254
|View full text |Cite
|
Sign up to set email alerts
|

The Initial Domestication of Goats ( Capra hircus ) in the Zagros Mountains 10,000 Years Ago

Abstract: Initial goat domestication is documented in the highlands of western Iran at 10,000 calibrated calendar years ago. Metrical analyses of patterns of sexual dimorphism in modern wild goat skeletons (Capra hircus aegagrus) allow sex-specific age curves to be computed for archaeofaunal assemblages. A distinct shift to selective harvesting of subadult males marks initial human management and the transition from hunting to herding of the species. Direct accelerator mass spectrometry radiocarbon dates on skeletal ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
358
1
9

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 617 publications
(376 citation statements)
references
References 6 publications
8
358
1
9
Order By: Relevance
“…The domestic goat (Capra hircus) is widely reared throughout the world, especially in China, India and other developing countries 1 . Goats serve as an important source of meat, milk, fiber and pelts, and have also fulfilled agricultural, economic, cultural and even religious roles since very early times in human civilization 2 .…”
Section: A R T I C L E Smentioning
confidence: 99%
“…The domestic goat (Capra hircus) is widely reared throughout the world, especially in China, India and other developing countries 1 . Goats serve as an important source of meat, milk, fiber and pelts, and have also fulfilled agricultural, economic, cultural and even religious roles since very early times in human civilization 2 .…”
Section: A R T I C L E Smentioning
confidence: 99%
“…Indeed, when the level of breed differentiation based on the present Y-chromosomal data was compared with that of 20 autosomal microsatellite data from the same set of breeds, and the four-times smaller effective population size on the Y-chromosome was taken into account, we found that genetic drift has produced a five-times wider divergence between the breeds for the Y-chromosome than for the autosomes. An intensive culling of breeding males was practiced during animal domestication in prehistoric times (Zeder and Hesse, 2000) and present-day artificial insemination bulls typically descend from only a few elite bulls. On the other hand, male-mediated crossbreeding of locally raised indigenous cattle breeds may have accelerated the loss of original Y-chromosomal haplotypes.…”
Section: Discussionmentioning
confidence: 99%
“…From the number of identified specimens, domestic sheep (Ovis aries) and goats (Capra hircus) predominate the assemblage at 51% overall, while cattle (Bos taurus) and pigs (Sus scrofa) make up 21% and 25%, respectively. This represents the typical suite of Near Eastern food animals since about 10,000 years ago (Zeder and Hesse 2000), although the relative proportion of cattle remains is quite high when compared to that at other contemporary sites (see table A2). While only 2% of the Domuztepe assemblage represents bones of wild animals, bones recovered in flotation suggest that fish played a bigger role than the handpicked assemblage indicates and may have actually made up 5% or more of the entire assemblage.…”
Section: Botanical and Faunal Analysesmentioning
confidence: 99%